2017
DOI: 10.3390/ph10010031
|View full text |Cite
|
Sign up to set email alerts
|

Anacardic Acid Constituents from Cashew Nut Shell Liquid: NMR Characterization and the Effect of Unsaturation on Its Biological Activities

Abstract: Anacardic acids are the main constituents of natural cashew nut shell liquid (CNSL), obtained via the extraction of cashew shells with hexane at room temperature. This raw material presents high technological potential due to its various biological properties. The main components of CNSL are the anacardic acids, salicylic acid derivatives presenting a side chain of fifteen carbon atoms with different degrees of unsaturation (monoene–15:1, diene–15:2, and triene–15:3). Each constituent was isolated by column ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
5

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(46 citation statements)
references
References 20 publications
1
38
0
5
Order By: Relevance
“…Strikingly, 15:2 anacardic acid levels were markedly increased in all ICT (62-fold, P = .0077, Welch's two-sample t test) and IN (94-fold, P = .0288) responders. Anacardic acid is an alkyl derivative of salicylic acid and produced in the nutshell of cashews [31] and also in mangos. Interestingly, anacardic acids stimulate phagocytes and can augment bactericidal activity [32] , [33] .…”
Section: Resultsmentioning
confidence: 99%
“…Strikingly, 15:2 anacardic acid levels were markedly increased in all ICT (62-fold, P = .0077, Welch's two-sample t test) and IN (94-fold, P = .0288) responders. Anacardic acid is an alkyl derivative of salicylic acid and produced in the nutshell of cashews [31] and also in mangos. Interestingly, anacardic acids stimulate phagocytes and can augment bactericidal activity [32] , [33] .…”
Section: Resultsmentioning
confidence: 99%
“…Cardanol and cardol are non-polar compounds typical of plants of the genus of the family Anacardiaceae, both in native and cultivated cultures. Anacardic acid, cardanol, cardol and methyl cardol, with different degrees of unsaturation (monoene-15:1, diene-15:2, and triene-15:3), were isolated from cashew (Anacardium occidentale), family Anacardiaceae (Morais et al, 2017;Fadeyi et al, 2015;Gómez-Caravaca et al, 2010). Thus, possibly a plant of the Anacardiaceae family, probably Anacardium occidentale and/or Mangifera indica, could be the resin source for this propolis.…”
Section: Resultsmentioning
confidence: 99%
“…In a landmark PMx and metagenomics study of patient's response to an immune checkpoint inhibitor (ICT), the metagenomic analysis of fecal samples showed the gut microbiome was enriched with Bacteroides caccae, while PMx analysis of fecal samples revealed that anacardic acid levels were increased in all ICT responders (62-fold, p = 0.0077). Anacardic acid is a derivative of salicylic acid and is found in cashews and mangos [94]. Anacardic acid has been shown to supplement bactericidal activity [95].…”
Section: Pmx Data and Gut Flora Metagenomics Datamentioning
confidence: 99%